(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article provides a definition and a brief description of the integrative method. This method was developed as a teaching technology of the foreign language to the adult users in the conditions of its functioning. The authors offer their own interpretation of the teaching method of the target language. Integrative method is considered as a set of the most effective and optimal teaching methods and techniques, that stimulate and activate the communicativecognitive activity of the secondary language personality. The article defines the basic idea of an integrative method and its main characteristics. The technology of a foreign language teaching in the conditions of its functioning based on the integrative teaching method is treated as innovative. This technology helps to optimize and intensify the teaching, stimulates the activity of the language cognition and provides motivation to the organization of communicativecognitive activity of the secondary language personality.